Pengaruh Kualitas Produk, Pelayanan, Lokasi dan Fasilitas terhadap Minat Nasabah untuk Menabung pada Bank BRI Unit Harapan Baru - Sektalonir Oscarini Wati Bhakti; Pransiska Diana (Politeknik Negeri Samarinda, 2022)
The research objective was to determine effect the quality of the product, service, location and facilities on the customer Interest in the Saving in BRI New Hope Bank. The method of data collection was done through by a questionnaire, distributed to 100 respondents, namely customers of the BRI New Hope Bank. The data obtained was then processed using the SPSS version 23 tool. The analysis of the research included the validity test, reliability test, multiple regression analysis hypothesis testing (t test, F test, and R2 test), and also the classical assumption test. The test results partially show that product quality and location do not have a positive and significant effect on interest in saving. While services and facilities have a positive and significant effect on interest in saving.